Case report: Pharmacokinetics of pembrolizumab in a patient with stage IV non–small cell lung cancer after a single 200 mg administration - de Vries, Fenna; Smit, Adrianus A. J.; Wolbink, Gertjan; de Vries, Annick; Loeff, Floris C.; Franssen, Eric J. F. (Frontiers in Oncology, 2023)
Background Pembrolizumab is a well-tolerated biologic agent with a potentially stable and durable anti-tumor response. Unfortunately, discontinuation of therapy can occur as a consequence of immune-related adverse effects (irAEs). These irAEs appear independent of dose and exposure. (1,2) However, this might result from pembrolizumab’s highly specific mechanism of action and the current dosing regimens in which an expensive drug is undesirably overdosed. A reassessment of the current and alternative dosing strategies is called to prevent this overdosing. However, the currently available pharmacokinetic (PK) and pharmacodynamic (PD) data to reassess these dosing strategies are insufficient. To highlight the importance of additional PK/PD studies, we present a case describing the complexity of pembrolizumab’s PK/PD after a single 200 mg pembrolizumab dose in a treatment-naive patient with non-small cell lung cancer (NSCLC). Case Description A 72-year-old male with stage IV NSCLC presented hepatotoxic symptoms nineteen days after receiving the first 200 mg pembrolizumab dose. Hence, pembrolizumab therapy was paused, and prednisolone therapy was initiated, which successfully inhibited the toxic effect of pembrolizumab. However, repeated flare-ups due to prednisolone tapering suggest that the toxic effect of pembrolizumab outlasted the presence of pembrolizumab in the bloodstream, thus suggesting that the T-cell-mediated immune response outlasts the PD-1 receptor occupancy by pembrolizumab, which challenges the need for the current fixed interval strategies and their stop criteria. Furthermore, a validated ELISA quantified pembrolizumab levels in 15 samples within 123 days after the administration. A shift in the pembrolizumab clearance rate was evident ensuing day 77 (0.6 µg/mL) after the administration. Pembrolizumab levels up to day 77 (9.1 – 0.6 µg/mL) strongly exhibited linear, first-order clearance (R2 = 0.991), while after day 77, accelerated non-linear clearance was observed. This transition from linear to non-linear clearance was most likely a result of full target receptor saturation to non-full target receptor saturation, in which the added effect of target-mediated drug disposition occurs. This suggests that the pembrolizumab drug targets were fully saturated at levels above 0.6 µg/mL, which is 43 to 61 times lower than the steady-state trough levels (Ctrough,ss) of the currently registered fixed-dosing regimens. (3–5)